The PI3K and AIB1 interaction is involved in estrogen treated breast cancer cells - Li, Zhixi; Deng, Xiaogeng; Wu, Gang; Qiu, Ronglin; Ju, Xueming; Wang, Youyu; Zhang, Jie (Cellular and Molecular Biology, 2018)
AIB1 was involved in the development and progression of breast cancer. Although it was found that AIB1 could be phosphorylated by some kinases including PI3K, the function of AIB1 and AKT interaction in breast cancer is not well defined. MCF-7 cells were transfected with pERE-Luc AKT and/or AIB1 plasmids, and then ERE luciferase activity in presence or absence of estrogen (E2) were measured. Plasmids containing PTEN and an PI3K inhibitor LY294002 were transfected into or treated cells to identify the interaction of PI3K/AKT and activation of AIB1, and examine their roles in cell cycle regulation. The AKT phosphorylation activity was evaluated by kinase assay using H2B as a substrate. The association between A1B1 and pS2 promoter was detected by the Chromatin Immunoprecipitation (ChIP) assay. AIB1 and AKT in the same complex were detected by Pull-down assay. IGF-1 can increase AIB1 recruitment to PS2 and enhance the ER-dependent transcription activity through the PI3K/AKT pathway. AIB1 associate with AKT to regulate cell cycle. The special relations concerning the AIB1 and AKT may arouse some new viewpoints for potential therapeutic targets in breast cancer.